Section 25(b) pesticide labels - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes what Section 25(b) minimum risk pesticides are and how their labels differ from other pesticides.
CEPEP 5/02, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Labeling; Pesticide containers; Pesticides -- Law and legislation